Pengaruh Debt to Asset Ratio Dan Long Term Debt to Equity Ratio Terhadap Harga Saham Pada PT. Merck Indonesia, Tbk - Alifiana Ayu Sakinah; Puji Muniarty; Aris Munandar (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the impact of PT Merck Indonesia, Tbk's debt-to-asset and long-term debt-to-equity ratios on stock prices from 2014 to 2023. This study makes use of secondary data collected from the following sources: the official website of the firm (https://www.merckgroup.com) and the annual financial statement (https://www.investing.com). Using SPSS version 24, the research utilizes a variety of statistical procedures to analyze the data. These methods include hypothesis testing, multiple linear regression analysis, and classical assumption tests. According to the results, long-term debt to equity ratios considerably affect stock prices, whereas debt to asset ratios have no effect at all. On top of that, PT Merck Indonesia, Tbk stock prices are heavily impacted by both ratios taken together